2020
DOI: 10.1093/oep/gpaa048
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a minimum wage change on the distribution of wages and household income

Abstract: We use distribution regression analysis to study the impact of a 6% increase in the Irish minimum wage on the distribution of hourly wages and household income. Wage inequality, measured by the ratio of wages in the 90th and 10th percentiles and the 75th and 25th percentiles, decreased by approximately 8 and 4%, respectively. The results point towards wage spillover effects up to the 30th percentile of the wage distribution. We show that minimum wage workers are spread throughout the household income distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…SeeBargain et al (2019) andRedmond et al (2020) for recent applications of this method to the effect of the minimum wage on the gender wage gap and on wage inequality.…”
mentioning
confidence: 99%
“…SeeBargain et al (2019) andRedmond et al (2020) for recent applications of this method to the effect of the minimum wage on the gender wage gap and on wage inequality.…”
mentioning
confidence: 99%
“…The nominal hourly minimum wage level is somewhat higher in Northern Ireland than in Ireland (IE) (Table 2.1). However, research (Redmond et al, 2021) has shown that only a small proportion of workers are at this level (6.8% to 10.6% in IE in 2022 ; 8% in NI [Francis-Devine, 2023]). Later chapters will look at the actual distribution of earnings by gender in the two jurisdictions.…”
Section: Tax Welfare Employment and Family Policiesmentioning
confidence: 99%
“…Indeed, Appendix Table B.1 shows that only a quarter of those in the lowest quintile of individual earnings were also in the lowest quintile of equivalised household disposable income, with a quarter also located in the highest two income quintiles. The reason for this is largely because many low earners have a higher earning partner or spouse, placing them in the middle or even the top of the distribution of household disposable income despite low levels of individual pay (Redmond et al, 2021). It is for this reason that increases in the minimum wage have been described as a 'blunt instrument' for boosting the incomes of those at the bottom of the income distribution (Dorris et al, 2022;Redmond, 2020;Low Pay Commission, 2018).…”
Section: Income Growth and Inequalitymentioning
confidence: 99%
“…It is for this reason that increases in the minimum wage have been described as a 'blunt instrument' for boosting the incomes of those at the bottom of the income distribution (Dorris et al, 2022;Redmond, 2020;Low Pay Commission, 2018). While limited in terms of its effect on low incomes, minimum wage policy has an important role in counteracting forces acting to increase earnings or wage inequality (Holton and O'Neill, 2017;Redmond et al, 2021), reducing the gender pay gap (Bargain et al, 2019) or limiting the extent to which employers with market power are able to capture gains from in-work transfers like the Working Families Payment (Joyce and Zilliak, 2020).…”
Section: Income Growth and Inequalitymentioning
confidence: 99%